Regeneration of Furcation Defects Treated with Porous Hydroxyapatite and Platelet-Rich Plasma: A Histological Study - Talwar, Avaneendra; Amin, Reshma (Journal of Health and Allied Sciences NU, 2020)
Introduction The alveolar bone, periodontal ligament (PDL), and cementum are the integral structural components invariably subject to changes during periodontal diseases. Many documents on animal and human studies state that the polypeptide growth factors (GFs) have a role in periodontal regeneration. The platelet-rich fibrin (PRF) is in use since the last decade. It has the potential of delivering GFs into vertical osseous defects. Human platelets contain platelet-derived growth factor and transforming growth factor-β in their α granules. These GFs are involved in wound healing and act as promoters of tissue regeneration. The study aimed to obtain histologic evidence, if any, of new attachment in humans, following treatment of osseous defects with 10-1055-s-0040-1714651_00084_ (HA) and PRF mix.Materials and Methods Five maxillary molar teeth with advanced bone loss were treated with porous 10-1055-s-0040-1714651_00084_ (PHA) mixed with PRF. Distobuccal roots were resected and studied histologically for evidence of bone formation, if any, at 1st, 3rd, and the 5th months.Results The PHA was completely resorbed in all the specimens. There was definitive evidence of bone formation at the 3rd month itself with mature lamellar bone with resting and reversal lines at the fifth postoperative month. There was no evidence of new cementum or PDL formation.Conclusion PRF in conjunction with osteoconductive materials prove to accelerate bone formation in vertical osseous defects.
Keywords: histology; periodontal regeneration; platelet-rich plasma